Evaluating Characteristics of Top and Bottom Performance: Online Versus In-Class. Issue 2 (2nd April 2016) - Fendler, Richard J.; Ruff, Craig; Shrikhande, Milind
ABSTRACT: This study compared the characteristics of students who excel (those in the top quarter of their class) and students who merely survive (bottom quarter of class) when attending a course either in-class or online. Student characteristics such as personal attributes (learning styles and gender), individual competence (grade point average), and major (nonquantitative or quantitative) may influence performance differently in each setting. This study shows that low-performing students, who typically need the most guidance in an online course, do in fact have traits that differ from those of low-performing students in-class. Accordingly, it is imperative that instructors develop proper materials and evaluation procedures aimed at helping low-achieving students succeed. However, because online education lacks face-to-face interaction, faculty may not realize that these differences exist.